Pengaruh Dosis dan Waktu Aplikasi Pupuk Kandang Terhadap Sifat Fisik, Kimia Tanah Dan Hasil Jagung (Zea Mays L.) - Putra, Anak Agung Gede; Karnata, I Nengah; Sukasana, I Wayan (Jurnal Ilmiah Sains Sosial, Kewirausahaan dan Kebudayaan, 2025)
This study aims to determine the effect of dose and time of manure application on physical and chemical properties of soil, and yield of corn (Zea mays L.). This study used a Randomized Block Design (RBD) with two factors, namely the dose of manure (0, 10, 20, 30 and 40 t ha-1) and the time of manure application (1, 3, and 5 weeks before planting). The results showed that the dose of manure 40 t ha-1 produced the highest harvest dry seed weight (7.17 t ha-1) which was 230.5% higher than the treatment without manure, but the high dry seed weight (1.66 t ha-1) was achieved at a dose of 30 t ha-1 which was not significantly different from the value in the 40 t ha-1 dose treatment. The value of the oven dry seed weight was 19.3% higher than the treatment without manure. The time of manure application did not significantly affect the growth, yield of corn and variables of physical and chemical properties of the soil, except for the soil water content at 42 days after planting. The relationship between manure dosage and harvest dry seed weight and oven dry seed weight ha-1 is linear. The results of this study can be used as a reference to increase corn productivity through effective use of manure.